Tabata training: one of the most energetically effective high-intensity intermittent training methods - Tabata, I. (The Journal of Physiological Sciences, 2019)
For decades, high-intensity interval/intermittent exercise training methods have been used by elite athletes to improve their performance in sports. One of the most effective training methods, i.e., `Tabata training,` is reviewed herein from the viewpoint of the energetics of exercise. The prior research describing the metabolic profile and effects of Tabata training is also summarized, with some historical anecdotes.